ANALYSIS OF METALS MINING SECTOR LINKAGE ON NATIONAL ECONOMIC - Triswan Suseno; Meitha Suciyanti; Nendaryono Madiutomo (Puslitbang tekMIRA, 2019)
Metals mining is one of the sectors that drives the national economy, and produced to meet the needs of human life. Almost all industries need this sector as an input either directly or indirectly, and each creation of the output from this sector requires input from many other industries. The role of this sector can be traced by calculating its spreading (downstream linkages) and its degree of sensitivity (upstream linkages) of any other sectors in the country. The data used for supporting this calculation comes from trade transactions between sectors that have been compiled into Indonesian input-output tables. The analysis objective is to find the impact of metals mining sector on the regional economy. The method is conducted through approach of input-output analysis. Based on the calculation using inputoutput table analysis, it appears that there are four sectors that almost all its domestic output able to fulfill the needs of other sectors in the country, i.e. tin processing, other metals processing, gold processing, and silver processing sector. In other words, these four sectors have a high downstream linkage to other sectors in the country. The upstream linkages of these four sectors are also quite large because almost all other sectors in the country utilize the products of these sectors, either directly or indirectly. While the output of copper processing sector almost entirely for exports, it indicates that the other industries in the country have not been able to capitalize on this sector products due to various constraints such as technologies and investment in the processing and purification. This means that the copper mining sector has a low downstream linkage to the other sectors in the country. While the upstream linkage of this sector is very small, because this sector is not much utilizing the products from other sectors in the country for the production process. The four sectors are more impactful since they have a high level of upstream and downstream linkages to the other industry sectors in the country compared to the copper mining sector.